Unilateral Epileptic Negative Myoclonus Following Focal Lesion of the Postcentral Cerebral Cortex Due to Acute Middle Cerebral Infarction - Song, In-Uk (Korean Neurological Association, 2006)
Here we report a patient who suffered an acute infarction of the contralateral postcentral cerebral cortex and subsequently developed unilateral partial epilepsy with negative myoclonus. The findings of brain magnetic resonance imaging, polygraphic recordings of the postcentral somatosensory area, and response to anticonvulsant treatment support the presence of a cause-and-effect relationship, thereby providing evidence for a pathophysiological substrate for epileptic negative myoclonus.